A Compilation of investigative reports on the Erap mansions - Davila, Karen; Hofilena, Chay Florentino; Kaimo, Mari.; Lingao, Ed.; Mangahas, Malou; Rimban, Luz.; Philippine Center for Investigative Journalism (Quezon City Philippine Center for Investigative Journalism, 2000)
A documentary by the Philippine Center for Investigative Journalism, with the Probe Team and The Correspondents, on the houses owned, occupied or frequented by former President Joseph Estrada and his families, numbering at least 17 pieces of choice property worth over P2 billion in Metro Manila, Baguio and Tagaytay.
Pabahay ni Erap (13 mins.) aired on The Probe Team (GMA-7) 22 Aug. 2000 -- Palasyo, kaninon (14 mins.) aired on The Correspondents (ABS-CBN) 23 Oct. 2000 -- Crony village (21 mins.) aired on The Correspondents (ABS-CBN) 20 Nov. 2000 -- Regalo (23 mins.) aired on the Correspondents (ABS-CBN) 27 Nov. 2000.
Except for "Crony village" and "Crony village II", all [segments] were produced by the PCIJ.
Title on container: Mga palasyo ni Erap : a compilation of investigative reports on President Estrada's mansions.
VHS. Also available in VCD format.
Keywords: Philippines -- History -- 1998-2001.